Mesenchymal stem cell-derived exosomes improve diabetes mellitus-induced myocardial injury and fibrosis via inhibition of TGF-Î²1/Smad2 signaling pathway - Lin, Yuan; Zhang, Fang; Lian, Xiao-fen; Peng, Wei-qun; Yin, Chao-yao (Cellular and Molecular Biology, 2019)
The aim of this study is to investigate the effect of mesenchymal stem cell (MSC)-derived exosomes on diabetes mellitus-induced myocardial injury, and the underlying mechanism. Thirty adult male Sprague Dawley rats were randomly assigned to three groups of ten rats each: normal control group, diabetic control group and MSC exosomes group. Exosomes were isolated from MSCs through gradient ultracentrifugation. With the exception of normal control, diabetes mellitus (DM) was induced in the rats with a single intraperitoneal injection of 30 mg/kg body weight streptozotocin (STZ) in 0.1 mol/L sodium citrate buffer. Rats in MSC exosomes group were intravenously injected with MSC-derived exosomes once a week for 12 weeks. Left ventricular collagen (LVC) level was measured using acid hydrolysis method. Fatty acid transporters (FATPs) and fatty acid beta oxidase (FA-Î²-oxidase) were determined using enzyme-linked immunosorbent assay (ELISA). Gene and protein expressions of TGF-Î² and Smad2 were determined using real-time quantitative polymerase chain reaction (qRT-PCR) and Western blotting. Flow cytometric analysis and Western blotting revealed positive expression of exosomal specific marker, CD63. The level of LVC was significantly higher in diabetic control group than in normal control group, but was significantly reduced after treatment with MSC-derived exosomes (p < 0.05). The levels of FATPs and FA-Î²-oxidase were significantly lower in diabetic control group than in normal control group (p < 0.05). However, treatment with MSC-derived exosomes significantly increased the levels of these proteins (p < 0.05). The levels of expression of TGF-Î²1 and Smad2 mRNAs were significantly higher in the diabetic control group than in normal control group, but were significantly reduced after treatment with MSC-derived exosomes (p < 0.05). The expressions of TGF-Î²1 and Smad2 proteins were also significantly upregulated in diabetic control group, when compared with normal control group (p < 0.05). However, treatment with MSC-derived exosomes significantly down-regulated the expression of these proteins (p < 0.05). The results obtained in this study indicate that MSC-derived exosomes improve DM-induced myocardial injury and fibrosis via inhibition of TGF-Î²1/Smad2 signaling pathway.